Searching for sustainability within public health policy: insights from an injury prevention perspective - Errington, Gail; Evans, Catrin; Watson, Michael W. (Oxford University Press, 2016)
Background: Sustaining public health programmes in the long-term is key to ensuring full manifestation of their intended benefits. Although an increasing interest in sustainability is apparent within the global literature, empirical studies from within the European setting are few. The factors that influence sustainability are generally conceptualized at three levels: programme level, the immediate context and the wider environment. To-date attention has focused primarily on the former two. Using a community-based child injury prevention programme in England as an exemplar, this paper explores the concept of sustainability within the wider policy environment, and considers the impact of this on local programmes. Methods: A content review of global and UK national public health policies (1981–2014) relevant to child safety was undertaken. Interviews were held with senior representatives of global and UK agencies involved in developing child safety policy. Results Forty-nine policies were reviewed. The term ‘sustain’, or its derivatives, featured in 36 (73%) of these. Its’ use however, related primarily to conservation of resources rather than continued programme operation. Potential mechanisms for supporting programme sustainability featured within some documents; however, the approach to sustainability was inconsistent between policies and over time. Policy stakeholders identified programme sustainability as relevant to their core business, but its’ conceptualization varied according to individual interpretation. Conclusions: Programme sustainability is poorly addressed within global and UK-based public health policy. Strengthening a national and international policy focus on sustainability and incorporating sustainability into public health planning frameworks may create a more supportive environment for local programmes.